2016
DOI: 10.1159/000444050
|View full text |Cite
|
Sign up to set email alerts
|

ING4 Inhibits Proliferation and Induces Apoptosis in Human Melanoma A375 Cells via the Fas/Caspase-8 Apoptosis Pathway

Abstract: Background: Inhibitor of growth 4 (ING4) plays a role in regulating the cell cycle, apoptosis, cell invasion and migration, but the mechanisms involved remain to be elucidated. Objective: To explore how ING4 affects human malignant melanoma A375 cells. Methods: Recombinant lentiviral vectors (A375/pLenO-GTP-ING4) were constructed and transfected into A375 cells (experimental group). The impact of ING4 on the proliferation and apoptosis of A375 cells was investigated in in vitro and in vivo experiments in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…In this study, we found that infection of VV- ING4 reduced the ratio of Bcl-2/Bax and induced the activation of Caspase 8/9/3 and PARP in SW1990 human pancreatic cancer cells (Figure 3D ), suggesting that Caspase-dependent apoptosis and the Bcl-2 family is participated in VV- ING4 -induced cytotoxicity. This finding is in line with a previous study which identified the Fas/Caspase-8 pathway as a mechanism of ING4-induced apoptosis in human melanoma cells [ 30 ]. Another potential mechanism by which ING4 induces apoptosis is promotion of p53.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found that infection of VV- ING4 reduced the ratio of Bcl-2/Bax and induced the activation of Caspase 8/9/3 and PARP in SW1990 human pancreatic cancer cells (Figure 3D ), suggesting that Caspase-dependent apoptosis and the Bcl-2 family is participated in VV- ING4 -induced cytotoxicity. This finding is in line with a previous study which identified the Fas/Caspase-8 pathway as a mechanism of ING4-induced apoptosis in human melanoma cells [ 30 ]. Another potential mechanism by which ING4 induces apoptosis is promotion of p53.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with our findings, the pivotal antiangiogenic role of ING4 via inhibition of VEGF, CD31, CD34 and MVD has been strongly evidenced. 20 , 21 , 24 , 30 The disseminating effect of OAd on tumor angiogenesis and tumor-driven vasculature has also been reported, 35 and disruption of VEGF pathway was found to increase the amplification and distribution of OAds in tumor microenviroments. 36 TRAIL has also been found to efficiently decrease blood vessel formation and VEGF-induced angiogenesis in the tumor tissues.…”
Section: Discussionmentioning
confidence: 89%
“… 12 , 13 , 14 Similarly, a particular advance has been demonstrated with ING4 in inducing apoptotic cell death, particularly via the caspase pathway, in tumor cells but not in normal cells. 19 , 20 , 21 , 22 , 23 , 24 , 30 Angiogenesis is also a vital process for tumor growth and malignant phenotype, and human HCC is characterized as a hypervascular tumor with a potential target for anti-angiogenesis therapy. 31 , 32 Mechanistically, activation of VEGF pathway and overexpression of endothelial vascular markers, in particular CD31, have been described as the central angiogenic factors, 7 , 33 and currently blockade of VEGF pathway is an active investigational approach to suppress HCC and other tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is also an important cause of high mortality. In addition, multidrug resistance has been reported in the chemotherapy of melanoma, leading to a very poor prognosis (13); thus, there is a need to identify novel therapeutic drugs and drug targets for melanoma.…”
Section: Introductionmentioning
confidence: 99%